MiRNAs: a call to arms that shapes the plasticity of tumor associated macrophages in breast cancer - Fogazzi, Valentina; Cosentino, Giulia; Sommariva, Michele; Galardi, Angela; Dell’Orto, Elisa; Pupa, Serenella; Taccioli, Cristian; Iorio, Marilena V. (Frontiers in Immunology, 2026)
Breast cancer (BC) remains a leading cause of cancer-related mortality, and a major contribution to tumor progression and resistance to therapies arise from tumor microenvironment (TME). Tumor is indeed able to shape a self-permissive TME, reprogramming the cellular components into allies. Tumor-associated macrophages (TAMs), abundant in BC TME, mainly acquire an immunosuppressive M2-like phenotype able to fuel tumor progression, immune evasion, metastasis and therapy resistance through a dynamic crosstalk with cancer cells. MicroRNAs, transferred via extracellular vesicles and exploited by the tumor to mold an immunesuppressive niche, act as central mediators of this bidirectional communication: tumor-derived miRNAs can reprogram macrophages toward an M2-like functional program, and TAM-derived miRNAs in turn promote and sustain cancer cell progression. This miRNA-orchestrated plasticity highlights TAMs as key TME regulators. Clinically, miRNA modulation offers promising strategies for TAM reprogramming, alongside their utility as prognostic biomarkers. Integrating miRNA-targeted TME interventions with conventional therapies holds the potential to overcome resistance in high-TAM BC subtypes.